Ensemble generique des criteres et indicateurs du CIFOR (CIRAD-Foret and CIFOR, 2000)
This manual provides a comprehensive set of criteria and indicators (C&I) for sustainable forest management based on CIFOR's research. This research was conducted by interdisciplinary teams of experts in large-scale natural forests managed for commercial timber production in Indonesia, Côte d'Ivoire, Brazil and Cameroon, with additional sites in Germany, Austria and USA. The use of the term 'generic template', for these C&I is intended to prevent them being confused with an ideal and universally applicable set of C&I. In term of the scope of applicability ('generic to what?'), it is envisaged that this template be used primarily for tropical natural forests managed for commercial purposes. Use of the term 'generic' also emphasises that the C&I in this set can be modified and customised to comply with local conditions. They could therefore be used both as a flexible set that is adaptable to all types of forest situations, and as an operational 'mother' set to be used by CIFOR's proposed CIMAT system (C&I Toolbox Series No.3). 'Generic' also implies that this C&I template can be employed by a variety of user groups, such as certification bodies, government officials, donors, forest managers, project managers, and scientists.